Microcreditarea ca instrument pentru incluziune socială - Arpinte, Daniel (Calitatea Vieții, 2015)
The paper investigates the potential of microcredit sector in Europe, and particularly in Romania, to provide support for vulnerable groups. Although at European level the microcredit sector is severely undeveloped, in Romania it has a great potential for development under social economy sector. The credit cooperatives and the non-banking financial institutions demonstrated during the last years, particularly under the economic turbulence period, their competitive advantages in addressing categories that are usually avoided by traditional loaning entities. The mutual aid associations, both for employees and for retired people, although do not provide microcredits, their lending activity has a significant impact, and they have a good potential to expand their activity in microcredit area. For this analysis have been used data from European reports and research projects conducted by RIQL, focused on evaluation of social economy sector, for analyses of social economy entities involved in providing loans to the potential vulnerable groups in order to evaluate their potential to develop their activities in this regard. Another evaluated aspect is the efficiency of European Structural Funds or other specific European instruments (like Jasmine and Jeremie) in supporting the sector development and its focus on social component. The article lists in its end the main weaknesses of the microcredit sector at European and national level.